Integrating Takaful into Tanzania's Universal Health Insurance Framework: Policy Insights from Indonesia - Issa G. Ahmed; Sylivia Aulila Lugereka; Edmund Zakayo (Balai Penelitian dan Pengembangan Agama Semarang, 2026)
Tanzania's transition toward Universal Health Coverage (UHC) under the Universal Health Insurance (UHI) Act faces persistent challenges: insurance coverage remains near fifteen percent of the population, and high out-of-pocket costs continue to expose vulnerable households to catastrophic expenditure. At the same time, Tanzania introduced Takaful guidelines in 2022, spurring growth in Shariah-compliant financial products. This article examines how Tanzania's NHIF and UHI reforms can draw on Takaful principles and on Indonesia's comparative experience to design more inclusive, faith-sensitive health insurance. Drawing on Tanzanian statutory documents, TIRA's Takaful Guidelines, and secondary literature on Indonesia's Jaminan Kesehatan Nasional (JKN), the study applies a normative legal approach combined with comparative case study analysis, within a conceptual framework linking social health insurance theory, Takaful principles, and principal-agent theory. Indonesia offers an instructive comparator, having reached over ninety-five percent population coverage while integrating Islamic microinsurance. The analysis indicates that although Tanzania continues to face gaps in financial protection and enrolment trust, its regulatory environment is now favourable for integrating Takaful-based pooling and Shariah governance into national implementation. On this basis, the article proposes three design pathways: accredited Takaful health plans, community-based micro-Takaful linked to the UHI Equity Fund, and Takaful top-up products. These pathways represent one of the first systematic attempts to connect Tanzania's UHI reform agenda with Indonesia's Takaful-JKN experience and, paired with safeguards against risk-pool fragmentation, may help deepen health coverage in Tanzania. Empirical research is still needed to test their effectiveness in practice.